Quantitative control of interfacial structure and thermal conductivity between diamond and copper via thermal diffusion of alloying element - Yizhe Cao; Bo Li; Lei Liu; Shaolong Li; Dongxu Hui; Shaodi Wang; Huiying Liu; Xin Li; Xin Zhang; Shengyin Zhou; Shufeng Li (Journal of Materials Research and Technology)
The thermal property of diamond/metal composites mainly depends on the chemical bonding and structure of interfacial layers between two heterogeneous materials. To improve the thermal property of the diamond/metal composites, a metallic carbide layer that bridging both crystal structure and thermal transport of heterogeneous interfaces is required, though the formation mechanism of such carbide interfaces during powder sintering remains under debate, particularly for the scenario of varying thermal diffusion. Here, systematic experiments of diamond/Cu–Cr composites have been conducted to unravel the effects of two important variables for thermal diffusion, temperature (800–1025 °C) and holding time (5–60 min), on the growth of chromium carbide interfaces and the resulting thermal conductivity. It is found that the main characteristics of chromium carbide layer is more related to the holding time, that is, prolonged thermal diffusion. The extraction of diamonds in as-sintered composites allows a detailed quantification of coating efficiency and crystallographic-facet-dependence of chromium carbide interfaces during diamond/metal reaction at varying temperature and holding times. It is found that the prolonged thermal diffusion is not as expected to deteriorate the thermal conductivity, and leads to a more densified structure with highest thermal conductivity instead (∼577 W/(m·K)). Furthermore, thermal diffusion of diamond/metal reaction is discussed based on theoretical models. We theoretically demonstrate that long thermal diffusion could enhance the thermal diffusivity for the composites and achieve ∼90.8% of theoretical thermal conductivity predicted by the Maxwell-Eucken model.